PENGEMBANGAN BAHAN AJAR “LESTARI” BERBASIS POTENSI LOKAL BAGI SISWA KELAS IV SD - Ervawaty Ervawaty; Fathul Zannah; Tazkiyatunnafs Elhawwa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The background of this research is based on the minimal integration of the richness of local potential of Katingan Regency in national textbooks, so that the learning of science at SDN 4 Kasongan Lama becomes less contextual for fourth grade students. The focus of the research problem is directed at the development and testing of the validity, effectiveness, and efficiency of integrated thematic teaching materials entitled